Distribution of ABO and Rh blood groups among people visiting tertiary hospital of Dibrugarh district of Assam, India - Gogoi, Jadumoni; Baruah , Abanti B. (International Journal of Research in Medical Sciences, 2023)
Background: Clinical application of blood grouping are many. Blood grouping are needed for blood transfusion, in preventing hemolytic disease, paternity dispute, medico legal cases, in knowing susceptibility to disease, and also necessary for genetic research. This study was carried out with an objective to provide data regarding distribution of ABO and Rh blood groups among people visiting various department of tertiary hospital of Dibrugarh district of Assam, India. Methods: Data of 200 subjects were collected and analyzed regarding ABO and Rh blood groups from 01 August 2021 to 31 July 2022 and reported in simple numbers and percentage. ABO and Rh blood group type is determined by glass slide method. Results: The most common blood group among the subject was O (33%), B (33%), A (23%) and AB (22%). Rh positivity among the subject was 93% and Rh negativity is 7%. Conclusions: The most common blood group among the subject was O positive and B positive and least common was AB negative.